Efeito da incorporação do nitrato de cério na atividade antifúngica e propriedades físico-mecânicas de resinas acrílicas termopolimerizadas - Freire, Isabelle Cristine de Melo (2017)
Objectives: To evaluate the antifungal activity of different cerium nitrate solutions, the physical-morphological properties by scanning electronic microscope (SEM), surface roughness (Sa and Sz), contact angle and color parameters (L*a*b*)] and the mechanical property (Vickers hardness) of a thermo polymerized acrylic resin incorporated with the solutions. Materials and methods: Cerium hexahydrate nitrate solutions (Ce (NO3) 3 • 6H2 O) were obtained in two types of solvents (a-10% DMSO and b-5% DMSO + 5% Tween 80). Minimum inhibitory concentration (MIC), minimum fungicidal concentration (MFC) were determined the by micro dilution assay and inhibition of Candida albicans (ATCC 90028) biofilms was performed in plates (n = 5) and in test specimens (n = 10). To evaluate the physical and mechanical properties, cylindrical specimens were made (10 mm X 4 mm) with acrylic non-incorporated (control group), incorporated with 20% of 16xCIM and 32xCIM DMSO + Cerium (DC) solution and incorporated with 20% of 16XCIM and 32xCIM DMSO + Tween + Cerium (DTC) solution. Specimens were analyzed by optical profilometry surface roughness assay (Sa and Sz) (n = 20), contact angle test () (n = 20), Vickers hardness test (n = 20) and determination of color parameters (L*, a* and b*) by spectrophotometry (n = 20). Data were descriptively analyzed and the Two-Way ANOVA (plate biofilm) and ANOVA (roughness, Vickers hardness, color parameters and contact angle) complemented by Tukey test (α = 0.05 for L* and α=0,01 for the others) and the inhibition of fungal adherence in the specimens was analyzed by the non-parametric Mann-Whitney U test (α = 0.05). Results: CIM and CFM concentration was 1625 uL/mL for both tested solutions. There was biofilms inhibition for all groups and DC and DTC groups showed inhibition values greater than 87% (24 hours) and 62% (48 hours), with statistically significant differences from the control group (Nystatin) in both ranges tested time (p <0.01). For the roughness, a statistically significant difference was found between the Control group (Sa = 0.052, Sz = 0.51) and the other groups, with the highest values of the groups DC 16xCIM (Sa = 0.224, Sz = 2.34) and DC 32xCIM (Sa = 0.202, Sz = 2.13). For the hardness, the control group (19.91) and the DC 16xCIM (18.72) presented difference of the other groups. At the contact angle, the DC 16xCIM group had the highest contact angle (80.49º), with no statistically significant difference from the control (77.16º); the DC 32xCIM group (59.42º) had the lowest contact angle. In the color analysis, the control group had the lowest L*, a* and b* parameters, with a statistically significant difference in relation to the other groups. Final Considerations: The evaluated solutions presented antifungal activity against Candida albicans in both planktonic and biofilm forms as well as reduction of biofilm adhesion to cerium nitrate modified acrylic resin in the DC 16xCIM and DC 32xCIM groups. However, these experimental resins presented alterations in all properties evaluated, with higher values of roughness and parameters * L a * and b * of color, and lower values of hardness and contact angle.